Microbial proliferation deteriorates the corrosion inhibition capability, lubricity, and stability of cutting fluid - Yuanyuan Shen; Wenkai Zhang; Lili Wu; Yaohua Dong; Guoqiang Guo; Lihua Dong; Zhangwei Guo (Frontiers in Microbiology)
Cutting fluid is a type of fluid used in the metal-cutting process. It is prone to microbial growth during use, which can lead to the deterioration of its various useful properties; however, the mechanism underlying this deterioration remains unclear. This study analyzed the microbial diversity of field-sampled cutting fluids, and those with higher levels of diversity were used to inoculate other fluid samples in order to further study the effects of microbial growth on the properties of cutting fluids. The results show that the surface of cutting fluid sampled from the tank of a machining tool tank contained predominantly aerobic bacteria, while the bottom mainly harbored anaerobic and facultative microorganisms, with Yarrowia lipolytica representing the dominant fungus. Some obligate anaerobic bacteria were also present in the cutting fluid. Organic acids secreted by anaerobic microbial activity reduced the pH of the cutting fluid, as well as its resistance to corrosion. The metabolic activity of the aerobic microorganisms also consumed certain key components of the cutting fluid, which ultimately further lowered its pH and resistance to corrosion. Moreover, the number of fungi increased significantly during the later stages of the experiment. The rolling and bridging action of the resulting fungal mycelium caused flocculation of the effective components in the cutting fluid, resulting in reduced lubricity and poor stability. This study provides a theoretical basis for developing more effective measures to inhibit microbial growth and delay the deterioration of cutting fluid, thereby helping to improve the technical quality of the metal-cutting industry.